Development of extra early field pea genotypes using inter-specific hybridization - PARIHAR, A K; DIXIT, G P; SINGH, ANIL KUMAR; KUMAR, NITIN; SINGH, N P (The Indian Journal of Agricultural Sciences, 2021)
.